Spatial and temporal variation in macroparasite communities of three-spined stickleback - Young, Rebecca E.; MacColl, Andrew D.C. (Cambridge University Press, 2016)
Patterns in parasite community structure are often observed in natural systems and an important question in parasite ecology is whether such patterns are repeatable across time and space. Field studies commonly look at spatial or temporal repeatability of patterns, but they are rarely investigated in conjunction. We use a large dataset on the macroparasites of the three-spined stickleback, Gasterosteus aculeatus L., collected from 14 locations on North Uist, Scotland over an 8-year period to investigate: (1) repeatability of patterns in parasite communities among populations and whether variation is consistent across years, (2) whether variation between years can be explained by climatic variation and progression of the season and (3) whether variation in habitat characteristics explain population differences. Differences in relative abundance and prevalence across populations were observed in a number of parasites investigated indicating a lack of consistency across years in numerous parasite community measures; however, differences between populations in the prevalence and abundance of some parasites were consistent throughout the study. Average temperature did not affect parasite community, and progression of the season was only significant for two of 13 community measures. Two of the six habitat characteristics investigated (pH and calcium concentration) significantly affected parasite presence.